Metodologias Ativas: o uso de videoaula como ferramenta didática no ensino de matemática com alunos de escolas públicas - Moura Filho, José Haito de (2019)
This study aimed to contribute to the teaching practice of the mathematics teacher within the classroom through the active methodology: The inverted classroom. Using video lessons as pedagogical tool we seek to apply the use of the Information and Communication Technologies (ICTs) in mathematics learning in basic education. We seek to analyze public politics of the teachers education for the use of ICTs; Oppose the guidelines provided in the courses of continuing training with the teaching practice and verify the way in which the mathematics teacher can organize a teaching practice with the use of the video lesson. We also try to answer the following investigation question: What is the possibility of the basic Teaccher's education to use the video lessons as a teaching tool in the organization of pedagogical practice for teaching mathematics? The research has a qualitative approach with intervention, with the use of active methodologies of a descriptive and interpretative nature.